Some mechanisms for wound healing enhancing effects of bitter gourd (Momordica charantia L.) extract in diabetic rats - Rezaeizadeh, Alireza (2013)
Wound healing is greatly delayed in diabetes mellitus. About 15-25% of patients with diabetes will suffer a wound problem in their lifetime. The aim of the current research was to determine the effects of Momordica charantia L. (MC) whole fruit extract on wound healing in streptozotocin (STZ)-induced diabetes in neonatal rats. The antioxidant activity of water, methanolic, and chloroformic extract of the whole fruit of MC extracts was determined by ferric thiocyanate (FTC), thiobarbituric acid (TBA), free radical scavenging activity (DPPH). Total phenol and flavonoid components were measured as well. The malondialdehyde (MDA) level of wound tissue and serum was determined. The level of endogenous defense enzymes (catalase,superoxide desmotase, and glutathione peroxidase) was determined.Diabetes mellitus was induced in 160 one day-old male Sprague-Dawley ratsby injection of STZ (85 mg/kg). Twelve weeks later a 3 cm2 wound was placed in the back of each rat and the wounds were treated 2 times per day with either the topical MC aqueous extract (DMT) or vehicle alone (DV). In a parallel experiment some diabetic animals were treated with either oral MC (DMO, 20mg/kg) or both. Diabetic rats treated by povidone iodine, glibenclamide, or a combination of both were used as positive control groups, these were termed diabetic plus glibenclamide (DPG), diabetic plus povidine iodine (DPP), or diabetic plus glibenclamide and povidine iodine (DPM).Similarly treated non diabetic animals acted as control.At termination, blood samples were collected to measure blood glucose and serum insulin level. Additionally to confirm the presence of diabetes intraperitoneal glucose tolerance tests (IPGTT) and intraperitoneal insulin tolerance tests (IPITT) were also performed. The animals were terminated on days 5, 10 and 15 and wound area, wound reepithelialisation, granulation tissue fibroblast, myofibroblast, vessel number, inflammatory cell infiltrate, growth factors and collagen content was determined by immunohistochemistry (IHC). Hydroxyproline content was measured by colorimetry. Prior to the treatment of the wounds, antioxidant activity of three different types of MC extract (aqueous, methanolic and chloroformic) was measured by ferric thiocyanate (FTC), thiobarbituric acid (TBA), and diphenyl-picryl-hydrazyl (DPPH) methods. These assays showed that the antioxidant activity of aqueous extract of MC was significantly (P≤0.05) higherthanthe methanolic and chloroformic extract. For this reason the effect of the aqueous extract on diabetic control and wound healing (mentioned above) was determined.The effect of the aqueous extract of MC on diabetic control was determined by measurement of the malondialdehyde (MDA) profile of plasma and wound. These studies showed that MDA level in serumand wound tissue was significantly (P≤0.05) highest in the DC group and this increase was prevented in the DMO and DMM treated groups. TheMC aqueous extract also improved glucose tolerance and increased insulin sensitivity in the treated diabetic rats. With regard to the effect on wound closure, MC has significantly improved the wound closure observed in the DC rats. The improvement in wound closure was also evident in the histological studies which showed an increase of collagen fibers, fibroblast and myofibroblast cells in the granulation tissue in diabetic animals treated with MC.Additionally, the studies on the growth factor level by ELISA and histological methods in wound area have illustrated that there was a significant increase in the growth factor’s level in the DMT and DMM groups as compared to DC group. In conclusion, the studies in this thesis indicate that the oral administration of aqueous extract of MC fruit was effective in reducing hyperglycemia and also manifested improvement of glucose tolerance and insulin sensitivity. The results of this research also showed that the topical use of aqueous extract of MC fruit capable to improve the wound in treated diabetic rats. Furthermore, oral administration of MC also alleviates damage induced by diabetes in some of the wound parameters in treated diabetic rats.